First observation of mutual energy transfer of Mn4+–Er3+via different excitation in Gd2ZnTiO6:Mn4+/Er3+ phosphors. Issue 35 (25th August 2017) - Liao, Jinsheng; Wang, Qi; Wen, He-Rui; Yuan, Huali; Liu, Sui-Jun; Fu, Junxiang; Qiu, Bao
Abstract : Mutual sensitized luminescence of Mn 4+ –Er 3+ are realized via different excitation in Gd2 ZnTiO6 :Mn 4+ /Er 3+ phosphors. The upconversion from Er 3+ to Mn 4+ is first observed under 980 nm excitation. The downshift from Mn 4+ to Er 3+ is observed under 335 nm. Abstract : Mutual energy transfer between rare earth ions and transition metal ions in a single luminescence material easily achieves multifunctions by altering the excitation wavelength. In this study, we first observe the mutual energy transfer process between Mn 4+ and Er 3+ via different excitations in Mn 4+ –Er 3+ co-doped Gd2 ZnTiO6 phosphors synthesized by a high temperature solid-state reaction. During the downshift energy transfer from Mn 4+ to Er 3+, the Gd2 ZnTiO6 :Mn 4+ /Er 3+ phosphor exhibits a strong near-infrared emission around 1529 nm with a wide excitation band extending from 250 to 550 nm. Based on Dexter's theory, the energy transfer mechanism mainly contributes to a dipole–dipole interaction between Mn 4+ and Er 3+ ions, which is responsible for the greatly enhanced emission at 1529 nm. Upon the upconversion energy transfer from Er 3+ to Mn 4+, the Gd2 ZnTiO6 :Mn 4+ /Er 3+ phosphor shows a deep red emission of Mn 4+ under 980 nm laser excitation. The energy transfer process from Er 3+ to Mn 4+ is fully demonstrated by variations in excitation power as well as luminescence lifetimes of 551 nm emission of Er 3+ . Two-photon processes and resonance energy transfer from Er 3+ to Mn 4+ are required to populate the 2 E emitting level of Mn 4+ .